Novel Ultra-thin Platinum Nanowires and Their Catalytic Applications - Wang, Jiaqing; Geng, Hongbo; Li, Xinming; Pan, Yue; Gu, Hongwei (Current Organic Chemistry, 2015)
In the rapidly developing areas of nanotechnology, nano-scale materials as heterogeneous catalysts in the synthesis of organic molecules have got more and more attentions. In this review, we will summarize the synthesis of a new type of ultrathin nanostructure via wet chemical method and several new catalytic applications to establish heterogeneous catalytic system in “green” environments. Further study shows that these materials have higher catalytic activity and selectivity than previously reported nanocrystal catalysts. This review intends to combine nanomaterials preparation and organic chemistry to find new catalysts for low-cost, efficient, highly selective chemical synthesis. The catalytic transformation of functional groups based on novel nanomaterials, can achieve not only
Keywords: Platinum nanowires